2013
DOI: 10.5935/01012800.20130008
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Injury in polytrauma patients

Abstract: A Injúria Renal Aguda (IRA) no contexto do paciente politraumatizado ocorre, na maioria das vezes, por uma conjuntura de fatores que passam por eventos correlacionados à ressus-citação volêmica inicial, ao grau de resposta inflamatória sistêmica associada ao trauma, ao uso de contraste iodado para procedimen-tos diagnósticos, à rabdomiólise e à síndro-me compartimental abdominal. Atualmente, passamos por uma fase de uniformização dos critérios diagnósticos da IRA com o Acute Kidney Injury Network (AKIN), sendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…36 Thus, elderly patients have a lower GFR, which may be associated with higher levels of cystatin C and an increased risk of cardiovascular events. 28 As most of the studies that performed the multivariate regression analysis [66.66% (n = 4)] 15 , 17 , 18 , 23 included age in this analysis, and nonetheless found a significant association between high levels of cystatin C and the development of adverse outcomes, it is possible to conclude that this association is age-independent. It should be noted that the two studies 20 , 25 that were included in the meta-analysis are among these studies that included age in the multivariate regression analysis, indicating that the association between high levels of cystatin C and any cause-related mortality observed in meta-analysis is age-independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Thus, elderly patients have a lower GFR, which may be associated with higher levels of cystatin C and an increased risk of cardiovascular events. 28 As most of the studies that performed the multivariate regression analysis [66.66% (n = 4)] 15 , 17 , 18 , 23 included age in this analysis, and nonetheless found a significant association between high levels of cystatin C and the development of adverse outcomes, it is possible to conclude that this association is age-independent. It should be noted that the two studies 20 , 25 that were included in the meta-analysis are among these studies that included age in the multivariate regression analysis, indicating that the association between high levels of cystatin C and any cause-related mortality observed in meta-analysis is age-independent.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is related to the fact that cystatin C presents a greater sensitivity for the detection of the initial stages of renal dysfunction than serum creatinine or creatinine-based GFR. 28 , 29 Several authors have already demonstrated that renal dysfunction is associated with an increased risk of cardiovascular events. 30 , 31 Thus, it is possible to suggest that patients who have normal renal function assessed by GFR based on creatinine or serum creatinine but who have high levels of cystatin C may present with renal dysfunction at an earlier stage, which could be associated with an increased risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The patient had a CT scan on admission to hospital, without radiological contrast, and throughout his hospital stay, he never received antibiotics, vasoactive drugs or NSAIDs, which are the substances most commonly connected to AKI [7][8][9][10][11]. It is important to note that the initial leukocytosis normalized rapidly, proving that it resulted of syndrome of the in lammatory response to stress [3]. It was considered that the AKI could have originated from medication secondary to the use of phenytoin, which, according to some previous related cases, could lead to nephrotoxicity [8,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Here we stress the progressive and acute nature of the worsening of his renal function (Graph 1), as this was a patient who had been in perfect previous health, without any history of glomerulopathies or auto-immune diseases. Other possibilities that were ruled out [Immediately right away] include: crush syndrome, rhabdomyolysis, compartment syndrome, shock with harm to haemodynamics, and sepsis, which could have happened because of the accident [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation